Learning in Medical School: Transition Issues, Strategy Use, and Self-Regulation - Reaume, Denise; Ropp, Tracey (Canadian Journal of Higher Education, 2005)
This qualitative study investigated how students adapt to medical school. Thirty-six medical students completed an e-mail survey exploring the transition from pre-medical to medical education, the use of learning strategies, and self-regulated learning practices. Their responses highlighted the challenges of medical education and the learning skills that lead to the successful mastery of course demands. Respondents identified volume of information as the major transition issue. Key strategies used were establishing balance, selectively targeting information, and controlling stress. Strong metacognitive abilities and other self-regulating activities were identified. Findings indicated that while students initially found the workload stressful, the implementation of specific learning skills facilitated the adjustment to medical school. The study provides information on how high achieving students learn when confronted with new academic demands.